Your pain, my gain? Estimating the trade relocation effects from civil conflict - Tobias Korn; Henry Stemmler (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2022)
We derive a novel estimation approach to quantify three-party relocation effects in a dyadic framework. Applied to the effects of civil conflicts on trade, we find robust evidence that importers substitute away from exporters that are engaged in conflict. This trade relocation persists after the resolution of a conflict. As a potential explanation for the longevity of this effect, we provide evidence that trade relocation increases the likelihood of the two countries signing a Preferential Trade Agreement, which persistently decreases their bilateral trade costs. A heterogeneity analysis suggests that trade relocation does not occur in the fuels sector, and that highly integrated supply chains are less likely to relocate. We derive our estimation approach from the structural gravity model of international trade, translating the triadic relationship between a conflict country and an exporter-importer pair into an estimable dyadic relationship. Our estimation approach can be adapted to either cover alternative unilateral shocks, e.g. natural disasters, or to analyze other bilateral dependent variables, e.g. migration or FDI flows.
Keywords: F14; D74; N41; 330; Conflict and trade; trade diversion; gravity estimation; general equilibrium